Restructuring finance to promote productive employment - Gerald Epstein (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2014)
Modern financial markets and institutions have grown massively in relation to the economy in the United States and elsewhere, and there is little evidence that in recent years their contributions to economic and social output justify the resources they capture and the risks they impose on society. Many policy options exist to limit finance's destructive excesses and to shrink its size. But while these efforts are important, more proactive measures to redirect financial activity is likely to be needed to achieve key social goals, such as employment generation and a successful transition to a fossil fuel limited economy. Refocusing financial institutions and financial activities toward providing investments in renewable energy and energy conservation provide an important example of reformed financial activity that both generate more and decent employment, while contributing to the production of key social goods. Abandoning the decades-long embrace of speculative finance and promoting socially efficient finance instead is a key imperative facing the United States and many other countries who adopted financial liberalization in the late twentieth century, with costly results.
Keywords: E24; E6; G1; Q54; 330; financialization; employment; green transformation